2012
DOI: 10.1007/s00268-012-1440-4
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Stromal Tumors: Case Series of 29 Patients Defining the Role of Imatinib Prior to Surgery

Abstract: Neoadjuvant imatinib for locally advanced GISTs is a safe concept for downsizing, improving resectability, and aiding organ-preserving surgery. It also improves the chance of long-term survival. Surgery, however, remains the cornerstone of curative treatment of GISTs even after neoadjuvant imatinib.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…The EFS and OS seen in this study are consistent with previously conducted studies [4,8,15], although the high rate of progression/unresectability on neoadjuvant IM (20 %) seen with this study is previously not reported. Potential reasons for this include the slightly lower prevalence of stomach GIST and exon 11 mutants in our study compared to previous studies and higher % of the KIT/PDGFRA wild patients ('WT' category).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The EFS and OS seen in this study are consistent with previously conducted studies [4,8,15], although the high rate of progression/unresectability on neoadjuvant IM (20 %) seen with this study is previously not reported. Potential reasons for this include the slightly lower prevalence of stomach GIST and exon 11 mutants in our study compared to previous studies and higher % of the KIT/PDGFRA wild patients ('WT' category).…”
Section: Discussionsupporting
confidence: 94%
“…However, patients with GIST may be locally advanced/ unresectable at presentation or present in locations that entail morbid curative resections like rectum, duodenum or oesophagus. This category of patients has been the focus of recent studies elaborating the role of neoadjuvant or preoperative IM followed by evaluation for surgery [4][5][6]. While the phase II RTOG 0132 trial evaluated IM (600 mg/day) prospectively [7], the largest experience for neoadjuvant IM comes from the EORTC-STBSG analysis of 161 patients with locally advanced GIST [8].…”
Section: Introductionmentioning
confidence: 99%
“…Our results differ from the RTOG 0132 phase 2 trial in which 83% of patients had SD amongst the 31 patients with primary GIST and lesser PR rates. This is possibly due to the shorter duration of neoadjuvant IM given in this trial (8)(9)(10)(11)(12) weeks) compared to our study (12).…”
Section: Discussionmentioning
confidence: 43%
“…Neoadjuvant imatinib: longer the better, need to modify risk stratification for adjuvant imatinib spillage of tumor cells (8)(9)(10). There is growing evidence for neoadjuvant IM therapy in terms of disease free survival (DFS) and overall survival (OS), with major evidence of benefit shown in the EORTC-STBSG retrospective analysis (11)(12)(13)(14)(15).…”
Section: Original Articlementioning
confidence: 99%
“…Recent studies have demonstrated the importance of neoadjuvant therapy on locally advanced/ unresectable GIST or tumors present in complicated anatomical locations such as rectum, duodenum, or esophagus [36-38]. Patients with rectal, duodenal, or other GIST may be a good target population for neoadjuvant therapy because preservation of organ functions and avoiding enlarging the operative extent such as total gastrectomy or PD.…”
Section: Discussionmentioning
confidence: 99%